Playing God : the Bible on the Broadway stage - Bial, Henry, 1970- (Ann Arbor Michigan : University of Michigan Press, 2015)
Focuses on successful productions and notable flops that highlight the difficulties in adapting the Old and New Testaments for the stage, requiring a balance of religious and commercial considerations through a blend of spectacle, authenticity, sincerity, and irony.
Faith-based initiatives -- Ben-Hur, Biblical fan fiction -- In the beginning : theatrical creations -- These are the generations of Noah -- Why do the righteous suffer -- Jesus Christ, Broadway star -- Hard job being God.
Includes bibliographical references (pages 221-237) and index.
Keywords: Theater -- New York (State) -- New York -- History -- 20th century; Bible plays, American -- History and criticism; Bible -- In literature